RESPON PERTUMBUHAN DAN PRODUKSI TANAMAN JAGUNG (Zea mays L.) TERHADAP PEMBERIAN PUPUK KANDANG AYAM DAN PUPUK ORGANIK CAIR PLUS - Hadriman Khair; M.Syufrin Pasaribu; Ebdi Suprapto (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2013)
This study aims to determine the growth and yield response of corn ( Zea mays L. ) on chicken manure and liquid organic fertilizer plus . The design used was a Randoimized Block Design Factorial with two factors studied, namely : Chicken Manure Factor ( K ) consists of 3 levels and consists of K0 = 0 kg / plot , K1 = 1.5 kg / plot and K2 = 3 kg / plot. Factor Plus Liquid Organic Fertilizer ( Sea Horse Star ) ( B ) is divided into 4 levels without giving B0 = B1 = 3 ml / l of water , B2 = 6 ml / l of water and B3 = 9 ml / l of water. The parameters measured were plant height ( cm ), number of leaves ( blade ), days to flowering ( days ), ear length ( cm ) , cob weight per sample ( g ), weight of cobs per plot ( kg , number of seeds per cob ( seed ) and dry weight of seeds per plot ( g ). Key words: Growth, response, corn, organic, fertilizer